Transformation and fate of sulphur during steam gasification of a spent tyre pyrolysis char. (1st August 2022) - Zhang, Juan; Zhu, Mingming; Jones, Isabelle; Onyeka Okoye, Chiemeka; Zhang, Zhezi; Gao, Jian; Zhang, Dongke
Highlights: Steam promoted the release of S to gas phase from char as temperature increased. Organic S contents increased with increasing gasification temperature and time. Aliphatic sulphide converted to more stable thiophene at high temperature. Sulphone and sulphoxide converted into each other in reversible redox reactions. Sx and COS were transferred to sulphone and sulphoxide during steam gasification. Abstract: The transformation of sulphur (S) during steam gasification of a spent tyre pyrolysis char (STPC) was investigated by tracing the evolution of S species and their mass fractions through X-ray photoelectron spectroscopy analysis. The raw pyrolysis char and demineralised char samples were respectively reacted with steam in a vertical fixed bed reactor over a range of temperature (850, 950, 1050 °C), steam concentration (33.3, 50.0, 66.7 vol% steam in N2 ) and gasification time (0.5, 1, 2, 3, 4 h). The mass fraction of S in the partially gasified char increased with increasing time at 850 °C and 950 °C, but decreased at 1050 °C. However, the net amount of S retained in the gasified char relative to that in the raw STPC decreased with increasing mass loss ratio, implying that S loss was faster than carbon consumption. The dominant S species in the pyrolysis char were aliphatic sulphide and ZnS. After steam gasification, more than 80% S species in the gasified chars were in the form of organic S. The proportion of organic S increased while that of inorganic S decreased with increasing gasification time and temperature, regardless of steam concentration. Thiophene, aliphatic sulphide, sulphone and sulphoxide became the main organic S species while ZnS and sulphate were the dominant inorganic S species. Aliphatic sulphide, sulphone and sulphoxide were converted to more thermally stable thiophene. Sx released from ZnS or COS produced from CaSO4 reacted with the carbon matrix to form sulphone and sulphoxide in the gasified char.